Oxidative Stress and Male Infertility: Evidence From a Research Perspective - Ayad, Bashir; Omolaoye, Temidayo S.; Louw, Nicola; Ramsunder, Yashthi; Skosana, Bongekile T.; Oyeipo, Peter I.; Du Plessis, Stefan S. (Frontiers in Reproductive Health, 2022)
Male fertility potential can be influenced by a variety of conditions that frequently coincide. Spermatozoa are particularly susceptible to oxidative damage due to their limited antioxidant capacity and cell membrane rich in polyunsaturated fatty acids (PUFAs). The role of oxidative stress (OS) in the etiology of male infertility has been the primary focus of our Stellenbosch University Reproductive Research Group (SURRG) over the last 10 years. This review aims to provide a novel insight into the impact of OS on spermatozoa and male reproductive function by reviewing the OS-related findings from a wide variety of studies conducted in our laboratory, along with those emerging from other investigators. We will provide a concise overview of the production of reactive oxygen species (ROS) and the development of OS in the male reproductive tract along with the physiological and pathological effects thereof on male reproductive functions. Recent advances in methods and techniques used for the assessment of OS will also be highlighted. We will furthermore consider the current evidence regarding the association between OS and ejaculatory abstinence period, as well as the potential mechanisms involved in the pathophysiology of various systemic diseases such as obesity, insulin resistance, hypertension, and certain mental health disorders which have been shown to cause OS induced male infertility. Finally, special emphasis will be placed on the potential for transferring and incorporating research findings emanating from different experimental studies into clinical practice.